Tyrosine 308 Is Necessary for Ligand-directed G(s) Protein-biased Signaling of β(2)-Adrenoceptor - Woo, Anthony Yiu-Ho (American Society for Biochemistry and Molecular Biology, 2014)
Interaction of a given G protein-coupled receptor to multiple different G proteins is a widespread phenomenon. For instance, β(2)-adrenoceptor (β(2)-AR) couples dually to G(s) and G(i) proteins. Previous studies have shown that cAMP-dependent protein kinase (PKA)-mediated phosphorylation of β(2)-AR causes a switch in receptor coupling from G(s) to G(i). More recent studies have demonstrated that phosphorylation of β(2)-AR by G protein-coupled receptor kinases, particularly GRK2, markedly enhances the G(i) coupling. We have previously shown that although most β(2)-AR agonists cause both G(s) and G(i) activation, (R,R′)-fenoterol preferentially activates β(2)-AR-G(s) signaling. However, the structural basis for this functional selectivity remains elusive. Here, using docking simulation and site-directed mutagenesis, we defined Tyr-308 as the key amino acid residue on β(2)-AR essential for G(s)-biased signaling. Following stimulation with a β(2)-AR-G(s)-biased agonist (R,R′)-4′-aminofenoterol, the G(i) disruptor pertussis toxin produced no effects on the receptor-mediated ERK phosphorylation in HEK293 cells nor on the contractile response in cardiomyocytes expressing the wild-type β(2)-AR. Interestingly, Y308F substitution on β(2)-AR enabled (R,R′)-4′-aminofenoterol to activate G(i) and to produce these responses in a pertussis toxin-sensitive manner without altering β(2)-AR phosphorylation by PKA or G protein-coupled receptor kinases. These results indicate that, in addition to the phosphorylation status, the intrinsic structural feature of β(2)-AR plays a crucial role in the receptor coupling selectivity to G proteins. We conclude that specific interactions between the ligand and the Tyr-308 residue of β(2)-AR stabilize receptor conformations favoring the receptor-G(s) protein coupling and subsequently result in G(s)-biased agonism.